Design and manufacturing of a Vtol UAV by 3D printing - Tran, Anh Thong (2017)
In this project, 3D printed parts are strengthened and optimized to study the feasibility of FDM technology in producing parts for unmanned aerial vehicles (UAVs). Two methods of reinforcing were studied: CFRP reinforcement and fill compositing. For CFRP reinforcement, the primary testing method was three-point bending. The samples were reinforced by applying unidirectional CFRP prepregs on the top and bottom surfaces with adhesive. The results showed that the method was capable of significantly increase the load and stiffness of the part with consistency. For fill compositing method, L-shaped samples were used in a bending test setup. Initial results showed improvements in both load and stiffness. The methods to further alleviate possible errors during experiments and sample preparation can be achieved by further investigating the reinforcement technique on the suitability of application to the structure. Furthermore, topology optimization was done to realize the optimal designs for the L-shaped sample. For future studies, this can be implemented with reinforcing methods for optimal performance in strength to weight of the part.